Adaptive sliding mode backstepping control - based maximum torque per ampere control of permanent magnet-assisted synchronous reluctance motor via nonlinear disturbance observer. (July 2018) - Yu, Yang; Mi, Zengqiang; Zheng, Xiaoming; Chang, Da; Zheng, Xiaojiang; Sun, Chenjun
Combined with two approaches of sliding mode control and backstepping control, an adaptive sliding mode–based backstepping control scenario on the basis of nonlinear disturbance observer is proposed to complete maximum torque per ampere control for permanent magnet–assisted synchronous reluctance motor. The constraint relation of permanent magnet–assisted synchronous reluctance motor under maximum torque per ampere control is built, and the design of the controller is elaborated in detail. The uncertainties of modeling errors considering unmatched items are estimated through a presented nonlinear disturbance observer. The adaptive law reflecting the modeling error of the system is constructed. Globally asymptotic stability and convergence of the tracking error for the system are validated through Lyapunov stability criterion. Simulation and experimental results illustrate that external disturbances and uncertainties are observed correctly by nonlinear disturbance observer; the close-loop system controlled by the proposed controller can track the references rapidly and precisely, and the designed controller has a good robust ability.